Implementasi Model Pembelajaran Project Based Learning (PjBL) dalam Meningkatkan Kreativitas Belajar Siswa pada Mata Pelajaran Pendidikan Agama Islam di SMAN 1 Waru Sidoarjo - Abidatul Chasanah; Laila Badriyah; Eli Masnawati (Al-Munawwarah : Jurnal Pendidikan Islam, 2025)
The Project Based Learning (PjBL) model is a learning approach that actively involves students in the process of creating projects. The main principle is to develop students' skills in solving problems through implementing projects that produce concrete products. In practice, this model gives students the freedom to choose topics, conduct research, and complete specific projects. This method allows students to be directly involved, provides experiences similar to the real world, and produces relevant products. The steps in implementing the Project Based Learning model are problem presentation, planning, scheduling, monitoring, assessment, and evaluation. This research aims to explore the implementation of the Project Based Learning model in increasing student learning creativity at SMAN 1 Waru Sidoarjo, as well as the supporting and inhibiting factors. The research method used descriptive qualitative with data collection techniques in the form of interviews, observation and documentation. Data analysis includes collection, reduction, presentation and conclusions. The research results show that PjBL has been implemented well but requires further evaluation. Supporting factors include learning interactivity, student enthusiasm for learning, use of media and technology, and teacher support. Meanwhile, inhibiting factors include the family environment and limited study time.